2022
DOI: 10.1002/pds.5562
|View full text |Cite
|
Sign up to set email alerts
|

Identification of rheumatoid arthritis in German claims data using different algorithms: Validation by cross‐sectional patient‐reported survey data

Abstract: Objective: To evaluate different algorithms for the identification of rheumatoid arthritis (RA) in claims data using patient-reported diagnosis as reference.Methods: Within longitudinal data from a large German statutory health insurance, we selected a random sample of persons with ICD-10 code for RA (M05/M06) in ≥2 quarters in 2013. The sample was stratified for age, sex, and M05/M06. Persons were asked to confirm RA diagnosis (gold standard), which was linked to claims data given consent. Analyses were weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…Inpatient diagnostic procedures are not recorded as well. Seropositive RA may also be underestimated as ICD-10 coding in Germany is often unspecific 15. As women are over-represented in the BARMER statutory health insurance, but ILD is more common in men, this might lead to an underestimation of the number of persons with RA-ILD in this analysis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Inpatient diagnostic procedures are not recorded as well. Seropositive RA may also be underestimated as ICD-10 coding in Germany is often unspecific 15. As women are over-represented in the BARMER statutory health insurance, but ILD is more common in men, this might lead to an underestimation of the number of persons with RA-ILD in this analysis.…”
Section: Discussionmentioning
confidence: 97%
“…To increase the specificity of the RA diagnosis, we additionally required a DMARD therapy, which could have been prescribed at any time point prior to or during the index year. Our previous validation of the RA ICD-10 diagnosis in the BARMER claims data revealed that the requirement of a prescribed DMARD significantly increases the specificity 15. To increase the specificity of ILD diagnosis, we additionally required the performance of a lung diagnostic test (function tests, chest radiographs, high-resolution CT (HRCT) scans, bronchoscopy or bronchoalveolar lavage).…”
Section: Methodsmentioning
confidence: 99%
“…The validity of PsA diagnoses has not been investigated in these data. For RA, 81% of the persons with two German modification of the International Statistical Classification of Diseases (ICD-10-GM) codes of M05 or M06 in a large survey confirmed the diagnosis and 7.2% had another inflammatory rheumatic disorder, predominately PsA 11…”
Section: Methodsmentioning
confidence: 99%
“…Die Prävalenz bei Grellmann et al ist niedriger als in den anderen Routinedatenanalysen, weil nur die spezifischen ICD-10-Codes für RA M05.8, M06.0 und M06.8 eingeschlossen wurden. In der Versorgungsrealität werden aber am häufigsten die unspezifischen RA ICD-10-Codes M06.9 und M05.9 verwendet [24], sodass bei dieser Arbeit von einer Untererfassung von RA-Fällen ausgegangen werden muss. Bei den Selbstangaben der Befragten aus der NAKO-Studie ist eine Übererfassung durch häufige Verwendung des Begriffs "Rheuma" auch bei Fingerpolyarthrose oder Gicht möglich; hier ist die Abgrenzung im Rahmen einer Befragung schwierig, obgleich explizit nach rheumatoider Arthritis bzw.…”
Section: Rheumatoide Arthritisunclassified